DEVELOPING STUDENTS’ READING COMPREHENSION THROUGH CONTEXTUAL GUESSING - Fariska Wulandari (Jurnal Pendidikan Bahasa, 2016)
This research was aimed at developing students reading comprehension for D class first semester students at Polytechnic of Tonggak Equator Pontianak.This research was classroom action research which was set out in two cycles, they were the first and second cycle. The subject involved in this research included the students of D class, first semester students of Polytechnic of Tonggak Equator. In gathering the data, the researcher used some instruments, they were field note and test. The data of the students’ pre-test and progress test score were analyzed by using mean score and the data of observation was analyzed descriptively.The finding of this research were the students’ reading comprehension were developed from pre-test and progress test from cycle to cycle. The mean score of the students’ pre-test was 72. Then, the mean score of the students’ progress test in the 1st cycle was 84. Finally, the mean score of the students’ progress test in the 2nd cycle was 91.Keywords: developing, reading comprehension, contextual guessing.